The Flotation Methods of Industrial Wastewater Treatment (Eurasian Research Bulletin, 2022)
The article considers flotation methods for industrial wastewater treatment. As a result of experiments in wastewater treatment, various design schemes, applications and flotation methods have been developed. The froth flotation method was used to remove some insoluble and partially reduce the concentration of some solutes, and the froth separation method was used to remove the dissolved substances.